Survival and hormone production of isolated mouse follicles in three-dimensional artificial scaffolds after stimulation with bpV(HOpic) - Keckstein, Philip; Dittrich, Ralf; Bleisinger, Nathalie; Hoffmann, Inge; Beckmann, Matthias; Gebhardt, Albrecht; Schmid, Benjamin; Keckstein, Simon (Archives of Gynecology and Obstetrics, 2024)
Purpose: To preserve fertility before gonadotoxic therapy, ovarian tissue can be removed, cryopreserved, and transplanted back again after treatment. An alternative is the artificial ovary, in which the ovarian follicles are extracted from the tissue, which reduces the risk of reimplantation of potentially remaining malignant cells. The PTEN inhibitor bpV(HOpic) has been shown to activate human, bovine and alpacas ovarian follicles, and it is therefore considered a promising substance for developing the artificial ovary. The purpose of this study was to examine the impact of different scaffolds and the vanadate derivative bpV(HOpic) on mice follicle survival and hormone secretion over 10 days. Methods: A comparative analysis was performed, studying the survival rates (SR) of isolated mice follicle in four different groups that differed either in the scaffold (polycaprolactone scaffold versus polyethylene terephthalate membrane) or in the medium—bpV(HOpic) versus control medium. The observation period of the follicles was 10 days. On days 2, 6, and 10, the viability and morphology of the follicles were checked using fluorescence or confocal microscopy. Furthermore, hormone levels of estrogen (pmol/L) and progesterone (nmol/L) were determined. Results: When comparing the SR of follicles among the four groups, it was observed that on day 6, the study groups utilizing the polycaprolactone scaffold with bpV(HOpic) in the medium (SR: 0.48 ± 0.18; p = 0.004) or functionalized in the scaffold (SR: 0.50 ± 0.20; p = 0.003) exhibited significantly higher survival rates compared to the group using only the polyethylene terephthalate membrane (SR: 0). On day 10, a significantly higher survival rate was only noted when comparing the polycaprolactone scaffold with bpV(HOpic) in the medium to the polyethylene terephthalate membrane group (SR: 0.38 ± 0.20 versus 0; p = 0.007). Higher levels of progesterone were only significantly associated with better survival rates in the group with the polycaprolactone scaffold functionalized with bpV(HOpic) (p = 0.017). Conclusion: This study demonstrates that three-dimensional polycaprolactone scaffolds improve the survival rates of isolated mice follicles in comparison with a conventional polyethylene terephthalate membrane. The survival rates slightly improve with added bpV(HOpic). Furthermore, higher rates of progesterone were also partly associated with improved survival.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Artificial ovary; bpV(HOpic); Ovarian follicle